A case report of pregnant female with right eye acremonium keratitis - Noticewala, Vaibhavee; Shastri, Manisha; Desai, Rupalee; Sheikh, Khushnood (International Journal of Research in Medical Sciences, 2017)
Study report a case of a 22-years-old female with history of vegetative trauma in right eye with 7th running months of amenorrhoea (RMOA). She came after 10 days of trauma, with chief complaint of pain, watering and diminution of vision in right eye. Her visual acuity was PLPR4 in affected eye and 6/9 in other. Central corneal ulcer with abscess and hypopyon was noted with inability to see fundal glow. To study response of fungal keratitis to voriconazole and natamycin eye drop. Corneal tissue obtained by a corneal scrape was plated on Sabouraud’s agar, KOH mount, gram and giemsa staining was performed. SDA shows a filamentous colony of fungus is grown upon aerobic incubation at 37◦C for 5-7 days. Patient was treated with combination therapy of voriconazole and natamycin eye drop. Patient responded well to combination therapy of voriconazole and natamycin eye drop. Patient developed corneal healing with little amount of fibrosis. We lost patient on follow up after that. Patient responded well to combination therapy of voriconazole and natamycin eye drop. The most common risk factors for acremonium fungal keratitis is ocular trauma, and acremonium fungal keratitis might be treated better with natamycin and voriconazole than other alternatives. our results are clinically significant and may provide some useful information on the diagnosis and management of acremonium fungal keratitis.